Low-silicon SAPO-34 molecular sieve as well as preparation method and application thereof
The mixture of aluminum source, phosphorus source, silicon source and organic amine template agent added nano SAPO-34 molecular sieve seed crystals, and two-step variable temperature crystallization and in-situ etching methods have been successfully solved. It is difficult to synthesize high crystallization in the prior art. The problem of low-silicon SAPO-34 molecular sieve is simplified, and the purity and reproducibility of the product is improved, and is suitable for catalytic reactions and adsorption separation.
Patent Information
- Application Number
- CN202310796617.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
It is difficult to efficiently synthesize pure phase low-silicon SAPO-34 molecular sieve with high crystallinity, and the traditional methods are complex and have poor repetition.
Using a mixture of aluminum source, phosphorus source, silicon source and organic amine template agent plus nano SAPO-34 molecular sieve seeds, low-silicon SAPO with pure CHA crystal phase was prepared by two-step variable temperature crystallization and in-situ etching. -34 molecular sieve, using cheap triethylamine template agent and metal source to simplify the process flow.
The synthesis of high crystallinity pure phase low silicon SAPO-34 is achieved, the process flow is simplified, the purity and repetition of the product is improved, and it is suitable for catalytic reactions and adsorption separation applications.
Smart Images

Figure CN119219009A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical materials, and in particular relates to a low-silicon SAPO-34 molecular sieve and a preparation method and application thereof. Background Art
[0002] SAPO-34 is an octahedral small-pore silicon-aluminum-phosphorus molecular sieve with a chabazite (CHA) structure. It was first synthesized by Union Carbide Corporation in 1984. Its framework structure is composed of [SiO4] 0 、[AlO4] - , [PO4] + Three tetrahedral units are connected to each other. SAPO-34 has a three-dimensional pore structure with a pore diameter of about 0.38nm×0.38nm. Smaller gases such as ethylene, propylene, and butene can selectively pass through the SAPO-34 pores. SAPO-34 molecular sieve has moderate acidity, rich pore structure, and good hydrothermal and thermal stability, and exhibits excellent catalytic performance in the methanol to light olefins reaction.
[0003] Generally speaking, low silicon SAPO-34 molecular sieve refers to a crystal with Si / Al atomic ratio less than 0.17. Wilson et al.'s research shows that low silicon SAPO-34 has excellent MTO reaction performance in MTO catalytic reaction (Microporous and Mesoporous Materials, 1999, 29, 117-126), especially higher ethylene selectivity, which is significantly better than ZSM-5, and promotes the industrial development of low silicon SAPO-34 molecular sieve. However, it is difficult to synthesize pure phase low silicon SAPO-34 molecular sieve by traditional hydrothermal synthesis method, and SAPO-5 or SAPO-18 impurities often appear, or appear in the form of composite molecular sieve, CN106564912A discloses a SAPO-34 / SAPO-18 composite molecular sieve and its preparation method, CN104828842A discloses a preparation method of SAPO-5 / SAPO-34 composite molecular sieve, and such composite molecular sieves contain impurities, which greatly limits the application range of molecular sieves.
[0004] The literature (Microporous and Mesoporous Materials, 2009, 126, 1-7) mentions that there are generally the following methods for synthesizing low-silicon SAPO-34 molecular sieves: one is to add fluoride to promote the depolymerization of silicon species to synthesize low-silicon SAPO-34 molecular sieves; the second is to add a mineralizer hydrochloric acid to synthesize low-silicon SAPO-34 molecular sieves; the third is to first synthesize high-silicon molecular sieves, desiliconize and synthesize low-silicon SAPO-34 molecular sieves; CN106513036A discloses a low-silicon SAPO-34 molecular sieve and its preparation method and application, which requires the use of a seed guide liquid, and the method is relatively cumbersome. The above methods often have the problems of difficulty in synthesizing high-crystallinity pure phase SAPO-34 molecular sieves, poor repeatability and many steps.
[0005] Therefore, it is necessary to develop a more feasible method for synthesizing low-silicon SAPO-34 molecular sieves to obtain high-purity SAPO-34 molecular sieves. Summary of the invention
[0006] In view of this, the present invention provides a low-silicon SAPO-34 molecular sieve and a preparation method and application thereof, the main purpose of which is to solve the technical problems that high-crystallinity pure-phase low-silicon-aluminum ratio SAPO-34 molecular sieve is difficult to synthesize and the synthesis method is cumbersome.
[0007] In one aspect, the present invention provides a method for preparing a low-silicon SAPO-34 molecular sieve, the preparation method comprising the following steps:
[0008] a) mixing an aluminum source, a phosphorus source, a silicon source, an organic amine template R, a metal source A and water to obtain an initial gel mixture having the following molar ratio:
[0009] R:A:Al2O3:P2O5:SiO2:H2O=1.5~5.0:0.01~0.15:1.0:0.5~2.0:0.08~0.3:20~200;
[0011] b) adding nano SAPO-34 molecular sieve seed crystals to the initial gel mixture obtained in step a) to obtain a gel mixture II; the amount of the seed crystals added is 0.1 to 3 wt% of the dry weight of the initial gel mixture;
[0012] c) placing the gel mixture II obtained in step b) into a reaction kettle, sealing it, heating it to 120-170° C. in a rotary oven, and performing rotational crystallization for 0.5-24 hours;
[0013] d) After step c) is completed, the temperature is raised to 180-220° C. and rotationally crystallized for 1-24 hours;
[0014] e) After step d) is completed, the temperature is lowered to 20-100° C. and rotated for 0.1-6 hours;
[0015] f) After the crystallization in step e) is completed, the obtained solid product is separated, washed and dried to obtain the low-silicon SAPO-34 molecular sieve.
[0016] In the initial gel mixture of step a) of the present invention, the amount of aluminum source added is calculated as the number of moles of Al2O3, the amount of phosphorus source added is calculated as the number of moles of P2O5, and the amount of silicon source added is calculated as the number of moles of SiO2.
[0017] The preparation method of the low-silicon SAPO-34 molecular sieve provided by the present invention can use cheap template agents such as triethylamine, add a metal source, and adopt a two-step variable temperature crystallization strategy to synthesize a low-silicon SAPO-34 product with a pure CHA crystal phase. The low-silicon SAPO-34 product has the characteristics of being rich in metal inside and low in metal content on the outer surface; the low-silicon SAPO-34 product is then retained in the range of 20 to 100° C. for a specific time, so that in-situ etching of the synthesized product can be achieved, and the metal-rich area inside is etched into the liquid phase, and finally a molecular sieve product with a hollow interior is obtained.
[0018] Optionally, the molar ratio of the organic amine template R to the aluminum source is selected from any value of 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or any range between two values.
[0019] Preferably, the molar ratio of the organic amine template R to the aluminum source is R:Al2O3=2.5-4.0:1.0.
[0020] Optionally, the molar ratio of the metal source A to the aluminum source is any value selected from 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15 or any range value between two of them.
[0021] Preferably, the molar ratio of the metal source A to the aluminum source is A:Al2O3=0.01-0.1:1.0.
[0022] Optionally, the metal source A in step a) is selected from at least one of magnesium oxide, magnesium acetate, magnesium nitrate, manganese oxide, manganese acetate, manganese nitrate, nickel oxide, nickel acetate, nickel nitrate, chromium oxide, chromium acetate, chromium nitrate, zinc oxide, zinc acetate, zinc nitrate, cobalt oxide, cobalt acetate and cobalt nitrate.
[0023] Optionally, the metal content corresponding to the metal source A in the low-silicon SAPO-34 molecular sieve obtained in step f) is 0.01 to 1.2 wt%.
[0024] Optionally, the metal content corresponding to the metal source A of the low-silicon SAPO-34 molecular sieve obtained in step f) is selected from any value among 0.01wt%, 0.02wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.2wt% or any range value between two of them.
[0025] Preferably, the metal content corresponding to the metal source A in the low-silicon SAPO-34 molecular sieve obtained in step f) is 0.01 to 0.15 wt%.
[0026] Optionally, the amount of the seed crystals added in step b) is any value selected from 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2.0wt%, 2.2wt%, 2.5wt%, 2.8wt% and 3.0wt% on a dry basis in the initial gel mixture, or a range value between any two of them.
[0027] Preferably, the amount of the seed crystals added in step b) is 0.1 to 1.5 wt % of the dry weight of the initial gel mixture.
[0028] Optionally, the aluminum source in step a) is selected from at least one of pseudo-boehmite, aluminum isopropoxide, sodium aluminate, aluminum foil, aluminum hydroxide, aluminum salt, activated alumina, aluminum alkoxide, and metakaolin.
[0029] Optionally, the aluminum salt is selected from at least one of aluminum sulfate, aluminum chloride and aluminum nitrate.
[0030] Optionally, the phosphorus source is selected from at least one of phosphoric acid, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.
[0031] Optionally, the phosphoric acid is selected from at least one of orthophosphoric acid, metaphosphoric acid and phosphite.
[0032] Optionally, the silicon source is selected from at least one of tetraethyl orthosilicate, silica sol, silica gel, white carbon black, silicic acid, water glass, diatomaceous earth and metakaolin.
[0033] Optionally, the organic amine template R is selected from at least one of cycloheximide, morpholine, diisopropylamine, diethanolamine, triethanolamine, diethylamine, pyridine, piperidine, cyclohexylamine, tetraethylammonium hydroxide, triethylamine, imidazole, methylimidazole, piperazine, and ethylenediamine.
[0034] Optionally, the particle size of the nano SAPO-34 molecular sieve seed crystals in step b) does not exceed 2 μm.
[0035] Preferably, the particle size of the nano SAPO-34 molecular sieve seed crystals in step b) is no more than 1 μm.
[0036] The nano SAPO-34 molecular sieve seed crystals of the present invention can be obtained by direct synthesis, or by post-processing a large-particle SAPO-34 molecular sieve, such as by ball milling.
[0037] Optionally, the silicon-aluminum molar ratio of the low-silicon SAPO-34 molecular sieve is Si / Al=0.06-0.17.
[0038] Optionally, the silicon-aluminum atomic ratio of the low-silicon SAPO-34 molecular sieve obtained in step f) is selected from any value among 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16 and 0.17, or any range between two values.
[0039] Preferably, the silicon-aluminum molar ratio of the low-silicon SAPO-34 molecular sieve is Si / Al=0.06-0.10.
[0040] Optionally, the temperature in step c) is selected from any value of 120°C, 125°C, 130°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C and 170°C, or any range therebetween.
[0041] Optionally, the time in step c) is selected from any value among 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, or any range between two of them.
[0042] Preferably, the temperature in step c) is 150-170° C., and the crystallization time is 10-15 hours.
[0043] Optionally, the temperature in step d) is selected from any value of 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C and 220°C, or any range therebetween.
[0044] Optionally, the time in step d) is selected from any value among 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, or any range between two of them.
[0045] Preferably, the temperature in step d) is 180-200° C. and the crystallization time is 10-12 h.
[0046] Optionally, the temperature in step e) is selected from any value of 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C and 100°C, or any range therebetween.
[0047] Optionally, the time in step e) is selected from any value among 0.1h, 0.5h, 1.0h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h or any range therebetween.
[0048] Preferably, the temperature in step e) is 20-60° C. and the residence time is 0.1-4 h.
[0049] In a second aspect, the present invention provides a low-silicon SAPO-34 molecular sieve, which is prepared by the above-mentioned preparation method.
[0050] In a third aspect, the present invention provides a molecular sieve material, which is a low-silicon SAPO-34 molecular sieve prepared by the above method or a material obtained by calcining the low-silicon SAPO-34 molecular sieve in air at 400°C to 700°C.
[0051] Optionally, the calcination temperature of the low-silicon SAPO-34 molecular sieve is selected from any value of 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C or any range therebetween.
[0052] In a fourth aspect, the present invention provides the use of the above molecular sieve material in catalytic reaction or adsorption separation.
[0053] Optionally, the catalytic reaction includes an acid-catalyzed reaction or an oxygen-containing compound conversion reaction to produce olefins.
[0054] Optionally, the adsorptive separation comprises adsorptive separation of methane and / or nitrogen and carbon dioxide.
[0055] Optionally, the molecular sieve material adsorbs carbon dioxide.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] (1) The method for preparing low-silicon SAPO-34 molecular sieve provided by the present invention solves the problem that SAPO-5 or SAPO-18 impurity crystals are easily generated during the synthesis of low-silicon SAPO-34, resulting in unqualified product quality. No HF or the like is required to be added, and the process is simple, the operation is convenient, the crystallization time is short, and a low-silicon SAPO-34 molecular sieve with high crystallinity and pure phase can be synthesized.
[0058] (2) The method for preparing low-silicon SAPO-34 molecular sieve provided by the present invention can be implemented by using cheap organic amines, such as triethylamine, etc., providing an economical method for synthesizing low-silicon SAPO-34.
[0059] (3) The low-silicon SAPO-34 molecular sieve provided by the present invention can significantly increase the single-pass life in the reaction of converting methanol or dimethyl ether into light olefins, greatly improve the selectivity of ethylene and propylene, and has industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 is the X-ray diffraction pattern of sample 1 in Example 1 of the present invention;
[0061] Figure 2 is a scanning electron microscope image of sample 1 in Example 1 of the present invention;
[0062] Figure 3 This is a scanning electron microscope image of sample 2 in comparative example 1 of the present invention;
[0063] Figure 4 This is the X-ray diffraction pattern of sample 3 in comparative example 2 of the present invention. DETAILED DESCRIPTION
[0064] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0065] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0066] The analysis method in the examples of this application is as follows:
[0067] X-ray powder diffraction phase analysis (XRD) was performed using an X'Pert PRO X-ray diffractometer from PANalytical of the Netherlands, with a Cu target, a Kα radiation source (λ=0.15418 nm), a voltage of 40 kV, and a current of 40 mA.
[0068] The bulk elemental composition of the samples was determined using a Magix 601X X-ray fluorescence analyzer (XRF) from Philips, the Netherlands, and the surface elemental composition of the samples was determined using a Thermo ESCALAB 250Xi photoelectron spectrometer (XPS).
[0069] The instrument used for scanning electron microscopy (SEM) testing is Hitachi SU8020 field emission scanning electron microscope with an accelerating voltage of 2 kV.
[0070] The MTO reaction performance of the catalyst was evaluated using a fixed bed device at normal pressure. The specific steps are as follows: the granulated catalyst powder of 40-60 mesh was calcined in an air atmosphere at 600°C for 4 hours to remove the template. 0.3g of catalyst was weighed and loaded into a quartz tube reactor, activated for 1 hour in a 30mL / min nitrogen atmosphere at 550°C, then cooled to 450°C and the raw gas was introduced for reaction. The methanol feed method was nitrogen-carried saturated methanol vapor feed, and the mass space velocity of methanol was 4h -1 . The product distribution was analyzed by Agilent GC7890 online gas chromatograph. The chromatographic column used was PoraPLOTQHT column and the detector used was FID detector. The obtained product distribution results were given in the form of mass percentage, with the total amount of hydrocarbons as 100. The dimethyl ether produced during the reaction was not included in the product distribution (reflected in the selectivity), but was regarded as unreacted raw material (reflected in the conversion rate). The single-pass reaction life was calculated based on the time when the methanol conversion rate was higher than 99%.
[0071] Preparation of Nano-SAPO-34 Seeds
[0072] Using the method mentioned in the literature (Chemical Communications, 2014, 50, 1845-1847), 15g of commercial SAPO-34 molecular sieve was calcined to remove the template agent, and 15g of deionized water was added. The mixture was placed in a ball mill and 3mm and 6mm mixed agate ball milling beads were added. A planetary ball mill (QM-3SP2) was used to ball mill for 360min at a speed of 550rpm / min. The obtained sample was placed in an oven at 110°C for drying. The particle size of the sample after ball milling was tested by a particle size analyzer, and the particle size was about 800nm. The preparation of seed crystals is not limited to the use of this method. Nano SAPO-34 molecular sieves (particle size less than 2μm, preferably less than 1μm) prepared by other methods can also be used directly as seed crystals.
[0073] Example 1: (Preparation of Sample 1)
[0074] 5g pseudo-boehmite (Al2O3 content 67.5wt%) and 22.9g deionized water were mixed and stirred evenly, and then 8g phosphoric acid (85wt%) and 1.8g silica sol (27.3wt%) were added dropwise to the mixture, and then 10g triethylamine was added after stirring evenly, and then 0.054g zinc oxide was added after sufficient stirring to obtain the initial gel mixture for synthesizing low-silicon SAPO-34 molecular sieve. The specific proportion of ingredients and crystallization conditions are shown in Table 1. Nano SAPO-34 seed crystals equivalent to 1.5wt% of the dry basis weight of the gel were added to the initial gel, and then transferred to a stainless steel autoclave after stirring evenly, and dynamically crystallized at 160℃ for 15h, heated to 200℃ for crystallization for 10h, and then cooled to 60℃ for 4h. After the crystallization was completed, the solid product was centrifuged, washed, and dried in air at 100℃ to obtain the low-silicon SAPO-34 molecular sieve, which was recorded as sample 1. X-ray diffraction analysis of sample 1 showed that the synthesized product had the characteristics of a single pure phase CHA structure (see X-ray spectrum for details). Figure 1 ). The elemental composition of the samples is listed in Table 2. The molar elemental composition of the solid detected by XRF is Al 0.498 Si 0.071 P 0.431 The atomic mass fraction of O2 and Zn is 0.028wt%. The surface element composition detected by XPS is Al 0.503 Si 0.101 P 0.396 O2, no Zn was detected, indicating that the surface Zn content is extremely low, and the Zn atomic mass fraction is less than 0.1%. The difference in bulk and surface elemental composition shows that the synthesized low-silicon SAPO-34 molecular sieve is rich in Si on the surface, and the metal Zn is mainly present inside the crystal. After staying at 60℃ for 4 hours, the metal Zn can be basically etched completely. The scanning electron microscope image shows that the morphology of the molecular sieve is cubic, and pores appear on the crystal surface, indicating that a certain degree of etching has occurred. The scanning electron microscope spectrum is shown in Figure 2 .
[0075] Examples 1-1 to 1-7: (Preparation of 1-1 to 1-7)
[0076] The difference between Examples 1-1 to 1-7 and Example 1 is that different raw materials are used. The rest is the same as Example 1. The specific ingredient ratios and crystallization conditions are shown in Table 1.
[0077] X-ray diffraction analysis and XRF elemental analysis were performed on the samples obtained in Examples 1-1 to 1-7 (sample 1-1, sample 1-2, sample 1-3, sample 1-4, sample 1-5, sample 1-6 and sample 1-7). The X-ray diffraction spectra of these samples were similar to those of Figure 1Similar features, and the solid element composition is close to that of Example 1; this indicates that a single pure phase low-silicon SAPO-34 molecular sieve has been successfully synthesized, and the XRD spectrum and element composition of the above sample are no longer attached repeatedly.
[0078] Example 1-8: (Preparation of Samples 1-8)
[0079] The difference between Example 1-8 and Example 1 is that the amount of nano SAPO-34 molecular sieve seed added is different, which is 0.1wt% of the dry weight in the initial gel mixture. The rest is the same as Example 1. The specific ingredient ratio and crystallization conditions are shown in Table 1.
[0080] X-ray diffraction analysis and XRF elemental analysis were performed on samples 1-8 obtained in Examples 1-8. The X-ray diffraction spectra of these samples were similar to those of Figure 1 Similar features, and the solid element composition is close to that of Example 1; this indicates that a single pure phase low-silicon SAPO-34 molecular sieve has been successfully synthesized, and the XRD spectrum and element composition of the above sample are no longer attached repeatedly.
[0081] SEM results show that the particle size of samples 1-8 is slightly larger than that of sample 1, indicating that increasing the amount of nano-SAPO-34 seed crystals added can effectively reduce the product particle size.
[0082] Comparative Example 1 (Preparation of Sample 2)
[0083] The difference between Comparative Example 1 and Example 1 is that there is no step e) in the synthesis method, and the obtained sample is recorded as Sample 2. X-ray diffraction analysis was performed on Sample 2, and the X-ray diffraction spectrum had the same Figure 1 Similar characteristics indicate that a single pure phase SAPO-34 molecular sieve was successfully synthesized, and the XRD spectra of the above samples are no longer attached.
[0084] The molar element composition of the solid detected by XRF is Al 0.498 Si 0.067 P 0.435 The atomic mass fraction of O2 and Zn is 0.494wt%. The surface element composition detected by XPS is Al 0.488 Si 0.089 P 0.423 O2, no Zn was detected, indicating that the surface Zn content is extremely low, and the Zn atomic mass fraction is less than 0.1wt%. The difference in bulk and surface element composition indicates that the synthesized low-silicon SAPO-34 molecular sieve is rich in Si on the surface, and the metal Zn is mainly present inside the crystal. The scanning electron microscope image shows that the morphology of the molecular sieve is cubic, and the crystal surface is flat and smooth. The scanning electron microscope spectrum is shown in Figure 3 .
[0085] By comparing the results of Example 1 with those of Comparative Example 1, it can be seen that step e) in the synthesis method of the present invention mainly involves etching, which can remove the metal element Zn from sample 1.
[0086] Comparative Example 2 (Preparation of Sample 3)
[0087] Comparative Example 2 is different from Example 1 in that the silicon dosage is increased, no metal source is added, and step e) is omitted. The obtained sample is recorded as Sample 3. X-ray diffraction analysis of Sample 3 shows that the XRD spectrum has an uneven baseline and broadened diffraction peaks, indicating that the synthesized product has the characteristics of AEI and CHA intergrowth structure (see X-ray spectrum). Figure 4 ).
[0088] By comparing the results of Example 1 and Comparative Example 2, it can be seen that adding a metal source to the synthetic raw material of the present invention can correct the crystal phase and obtain a single pure SAPO-34 crystal phase.
[0089] Comparative Example 3 (Preparation of Sample 4)
[0090] The difference between Comparative Example 3 and Example 1 is that: step d) the temperature is raised to 180°C for crystallization for 24 hours, and step e) the temperature is lowered to 20°C for 6 hours. The obtained sample is recorded as sample 4. X-ray diffraction analysis is performed on sample 4, and the X-ray diffraction spectrum has the same Figure 1 Similar characteristics; this indicates that a single pure phase SAPO-34 molecular sieve was successfully synthesized, and the XRD spectra of the above samples are no longer attached.
[0091] By comparing the results of Example 1 and Comparative Example 3, it can be seen that the solid product yield of Comparative Example 3 is greatly reduced, indicating that in the synthesis method of the present invention, extending the etching time will sacrifice the product yield.
[0092] Comparative Example 4 (Preparation of Sample 5)
[0093] Comparative Example 4 is different from Example 1 in that the amount of metal source added is 0.027 g, step d) the temperature is raised to 220°C for crystallization for 6 h, and step e) the temperature is lowered to 100°C for crystallization for 1 h. The obtained sample is recorded as Sample 5. X-ray diffraction analysis is performed on Sample 5. The X-ray diffraction spectrum has the same Figure 4 Similar characteristics indicate that the synthesized product has a co-growth structure of AEI and CHA, which means that the amount of metal source added in this synthesis method is too low and pure phase low-silicon SAPO-34 cannot be obtained.
[0094] Comparative Example 5 (Preparation of Sample 6)
[0095] Comparative Example 5 is different from Example 1 in that the amount of metal source added is 0.081 g, and step e) is cooled to 60°C for 4 hours. The obtained sample is recorded as Sample 6. X-ray diffraction analysis is performed on Sample 6. The X-ray diffraction spectrum has the same Figure 1Similar characteristics indicate that a single pure phase SAPO-34 molecular sieve was successfully synthesized, and the XRD spectra of the above samples are no longer attached.
[0096] By comparing the results of Example 1 and Comparative Example 5, it can be seen that the solid product yield of Comparative Example 5 is greatly reduced, indicating that increasing the amount of metal source added requires extending the etching time, which will sacrifice the yield.
[0097] Comparative Example 6 (Preparation of Sample 7)
[0098] Comparative Example 6 is different from Example 1 in that the amount of silica sol added is 0.36 g, the amount of nano-SAPO-34 seed added is 1.2 g, and step c) is heated to 120° C. for crystallization for 24 h. The obtained sample is recorded as Sample 7. X-ray diffraction analysis is performed on Sample 7. The X-ray diffraction spectrum has the same Figure 4 Similar characteristics indicate that the synthesized product has a co-growth structure of AEI and CHA, which means that reducing the silicon input and increasing the seed addition in this synthesis method cannot obtain pure phase low-silicon SAPO-34.
[0099] Comparative Example 7 (Preparation of Sample 8)
[0100] Comparative Example 7 is different from Example 1 in that the amount of silica sol added is 1.44 g, the amount of nano-SAPO-34 seed added is 0.42 g, and step c) is heated to 170°C for crystallization for 10 h. The obtained sample is recorded as Sample 8. X-ray diffraction analysis is performed on Sample 8. The X-ray diffraction spectrum has the same Figure 1 Similar characteristics indicate that a single pure phase SAPO-34 molecular sieve was successfully synthesized. The XRD spectra of the above samples are not repeated here. XRD measured the silicon-aluminum atomic molar ratio Si / Al = 0.10, which means that in this synthesis method, a proper reduction in the amount of silicon added and an increase in the amount of seed added can obtain a pure phase SAPO-34 with lower silicon content.
[0101] Example 2: (Preparation of Sample 9)
[0102] Mix 6.3g of pseudo-boehmite (Al2O3 content 67.5wt%) and 30.3g of deionized water, stir evenly, then drop 10g of phosphoric acid (85wt%) into the mixture, stir evenly, add 12.5g of triethylamine, stir thoroughly and add 0.671g of zinc oxide to obtain the initial gel mixture for synthesizing ZnAPO-34 molecular sieve. Add nano SAPO-34 seed crystals equivalent to 3wt% of the dry basis mass of the gel to the initial gel, stir evenly and transfer to a stainless steel autoclave, heat to 160°C and crystallize for 24h. After the crystallization is completed, centrifuge the solid product, wash, and dry in air at 100°C to obtain ZnAPO-34 molecular sieve, recorded as sample 9. X-ray diffraction analysis was performed on sample 9, and the X-ray diffraction spectrum had the same Figure 1Similar features, the XRD spectra of the above samples are not repeated. The molar element composition of the solid detected by XRF is Al 0.378 Zn 0.146 P 0.476 O2, which indicates that a single pure phase ZnAPO-34 molecular sieve was successfully synthesized.
[0103] Example 3: (Preparation of Sample 10)
[0104] Mix 6.3g of pseudo-boehmite (Al2O3 content 67.5wt%) and 28.7g of deionized water, stir evenly, then drop 10g of phosphoric acid (85wt%) and 2.2g of silica sol (27.3wt%) into the mixture, stir evenly, add 12.5g of triethylamine, stir thoroughly and add 0.067g of zinc oxide to obtain the initial gel mixture for synthesizing low-silicon SAPO-34 molecular sieve. Add nano-SAPO-34 seed crystals equivalent to 1.5wt% of the dry basis mass of the gel to the initial gel, stir evenly and transfer to a stainless steel autoclave, heat to 200℃ for crystallization for 10h, then cool to 20℃ and stay for 6h. After the crystallization is completed, the solid product is centrifuged, washed, and dried in air at 100℃ to obtain the low-silicon SAPO-34 molecular sieve, which is recorded as sample 10. X-ray diffraction analysis was performed on sample 10, and the X-ray diffraction spectrum has the same Figure 4 Similar features indicate that the synthesized product has an AEI and CHA intergrowth structure. The molar element composition of the solid detected by XRF is Al 0.489 Si 0.063 P 0.448 O2, and contains 0.565wt% Zn, indicating that without step c) the low-temperature crystallization stage, in step e) the metal element Zn cannot be etched away from the skeleton.
[0105] Comparative Example 8: (Preparation of Sample 11)
[0106] Comparative Example 8 is different from Example 3 in that step e) is omitted and the obtained sample is recorded as Sample 11. X-ray diffraction analysis is performed on Sample 11, and the X-ray diffraction spectrum has the same Figure 4 Similar features indicate that the synthesized product has an AEI and CHA intergrowth structure. The molar element composition of the solid detected by XRF is Al 0.492 Si 0.061 P 0.447 O2, and contains 0.604wt% Zn, which is close to the metal content in sample 10 obtained in step e).
[0107] By comparing the results of Example 3 and Comparative Example 8, it can be seen that when there is no step c) low-temperature crystallization stage, the presence or absence of step e) will not change the metal content in the solid product, further indicating that when there is no step c) low-temperature crystallization stage, the metal element Zn cannot be etched away from the skeleton.
[0108] Comparative Example 9: (Preparation of Sample 12)
[0109] Comparative Example 9 is different from Example 3 in that no metal source is added and step e) is omitted. The obtained sample is recorded as Sample 12. X-ray diffraction analysis is performed on Sample 12. The X-ray diffraction spectrum has the same Figure 4 Similar features indicate that the synthesized product has an AEI and CHA intergrowth structure, which means that without step c) the low-temperature crystallization stage, without the addition of a metal source, and without step e), a pure phase low-silicon SAPO-34 cannot be obtained.
[0110] Table 1. Molecular sieve synthesis ingredients and crystallization conditions
[0111]
[0112] Table 2. Elemental composition of samples
[0113]
[0114] Example 4 (Testing the reaction performance of methanol conversion to olefins)
[0115] The methanol-to-olefins reaction performance of sample 1, sample 2 and sample 10 was tested respectively, and the results are shown in Table 3. It can be seen that according to the method of the present application, the pure phase low-silicon SAPO-34 molecular sieve prepared by adding a metal source and two-stage variable temperature crystallization and the third-stage in-situ etching metal process is used as a catalyst for the methanol-to-olefins reaction, and the life and diene selectivity are greatly improved.
[0116] Table 3. Results of methanol conversion to olefins*
[0117]
[0118] *The reaction life is calculated based on the time when the methanol conversion rate is above 99%.
[0119] The selectivity refers to the highest selectivity when the methanol conversion rate is higher than 99%.
[0120] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing low-silicon SAPO-34 molecular sieve, characterized in that: The preparation method comprises at least the following steps: a) mixing an aluminum source, a phosphorus source, a silicon source, an organic amine template R, a metal source A and water to obtain an initial gel mixture having the following molar ratio: R:A:Al2O3:P2O5:SiO2:H2O=1.5~5.0:0.01~0.15:1.0:0.5~2.0:0.08~0.3:20~200; b) adding nano SAPO-34 molecular sieve seed crystals to the initial gel mixture obtained in step a) to obtain a gel mixture II; the amount of the seed crystals added is 0.1 to 3 wt% of the dry weight of the initial gel mixture; c) placing the gel mixture II obtained in step b) into a reaction kettle, sealing it, heating it to 120-170° C. in a rotary oven, and performing rotational crystallization for 0.5-24 hours; d) After step c) is completed, the temperature is raised to 180-220° C. and rotationally crystallized for 1-24 hours; e) After step d) is completed, the temperature is lowered to 20-100° C. and rotated for 0.1-6 hours; f) After the crystallization in step e) is completed, the obtained solid product is separated, washed and dried to obtain the low-silicon SAPO-34 molecular sieve.
2. The method for preparing low-silicon SAPO-34 molecular sieve according to claim 1, characterized in that: The metal source A in step a) is selected from at least one of magnesium oxide, magnesium acetate, magnesium nitrate, manganese oxide, manganese acetate, manganese nitrate, nickel oxide, nickel acetate, nickel nitrate, chromium oxide, chromium acetate, chromium nitrate, zinc oxide, zinc acetate, zinc nitrate, cobalt oxide, cobalt acetate and cobalt nitrate.
3. The method for preparing low-silicon SAPO-34 molecular sieve according to claim 1, characterized in that: The metal content corresponding to the metal source A in the low-silicon SAPO-34 molecular sieve obtained in step f) is 0.01-1.2 wt%.
4. The method for preparing low-silicon SAPO-34 molecular sieve according to claim 1, characterized in that: The metal content corresponding to the metal source A in the low-silicon SAPO-34 molecular sieve obtained in step f) is 0.01-0.15 wt%.
5. The method for preparing low-silicon SAPO-34 molecular sieve according to claim 1, characterized in that: The aluminum source in step a) is selected from at least one of sodium aluminate, aluminum foil, aluminum hydroxide, aluminum salt, activated alumina, aluminum alkoxide, and metakaolin; The phosphorus source is selected from at least one of orthophosphoric acid, metaphosphoric acid, phosphite, diammonium phosphate, and diammonium hydrogen phosphate; The silicon source is selected from at least one of tetraethyl orthosilicate, silica sol, silica gel, white carbon black, silicic acid, water glass, diatomaceous earth and metakaolin; The organic amine template R is selected from at least one of cycloheximide, morpholine, diisopropylamine, diethanolamine, triethanolamine, diethylamine, pyridine, piperidine, cyclohexylamine, tetraethylammonium hydroxide, triethylamine, imidazole, methylimidazole, piperazine, and ethylenediamine.
6. The method for preparing low-silicon SAPO-34 molecular sieve according to claim 1, characterized in that: The particle size of the nano SAPO-34 molecular sieve seed in step b) does not exceed 2 μm; The silicon-aluminum molar ratio of the low-silicon SAPO-34 molecular sieve is Si / Al=0.06-0.17; Preferably, the particle size of the nano SAPO-34 molecular sieve seed crystals in step b) is no more than 1 μm.
7. A low-silicon SAPO-34 molecular sieve, characterized in that: The molecular sieve is prepared by the preparation method described in any one of claims 1 to 6.
8. A molecular sieve material, characterized in that: The molecular sieve material is a low-silicon SAPO-34 molecular sieve prepared by the method described in any one of claims 1 to 6 or a material obtained by calcining the low-silicon SAPO-34 molecular sieve described in claim 7 in air at 400° C. to 700° C.
9. Use of the molecular sieve material according to claim 8 in catalytic reaction or adsorption separation.
10. Use of the molecular sieve material according to claim 9 in catalytic reaction or adsorption separation, characterized in that: The catalytic reaction includes an acid-catalyzed reaction or an oxygen-containing compound conversion reaction to produce olefins; preferably, the adsorption separation includes the adsorption separation of methane and / or nitrogen and carbon dioxide; preferably, the molecular sieve material adsorbs carbon dioxide.
Citation Information
Patent Citations
Preparation method of SAPO-5 and SAPO-34 symbiotic composite molecular sieve
CN104828842A
Low-silicon SAPO-34 molecular sieve as well as preparation method and application thereof
CN106513036A
Double-micropore SAPO (silicoaluminophosphate)-34 / SAPO-18 composite molecular sieve, and preparation method and application thereof
CN106564912A
Preparation and application method of low-silicon small particle SAPO-34 molecular sieve
CN109761243A
In-situ synthesis method and application of metal SAPO-34 molecular sieve
CN110124731A
Cited By
Modified methanol-to-olefin catalyst, preparation method, secondary modification method and application
CN121800201A
A modified methanol to olefin catalyst, a preparation method, a secondary modification method and application
CN121800201B